2015
DOI: 10.15237/gida.gd15011
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS of GRAFTING and HARVESTING TIME on SOME PHYSICAL AND CHEMICAL PARAMETERS of WATERMELON (Citrullus lanatus)

Abstract: Sebze yetifltiricili¤inde afl›l› fide kullan›m› önemli boyutlara ulaflm›flt›r. Afl›l› fide kullan›m›n›n ürün kalitesinde baz› farkl›l›klara yol açabilece¤i düflünülmektedir. Araflt›rma kapsam›nda üç farkl› anaç üzerine afl›lanm›fl iki farkl› karpuz çeflidinin iki hasat zaman›na göre baz› kalite parametreleri analiz edilmifltir. Ürünlerin kalite özelliklerinde afl›lama ve hasat zaman›na göre baz› farkl›l›klar görülmüfltür. Araflt›rma kapsam›nda analiz edilen örneklerin suda çözünür kuru madde (SÇKM), toplam kur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…The amount of K and Mg in the watermelon fruit did not show a significant difference between grafting treatments and varieties. Contrarily to the our results, Tokgöz et al (2015) indicated that grafting increased the amounts of K and Mg in the watermelon fruits.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The amount of K and Mg in the watermelon fruit did not show a significant difference between grafting treatments and varieties. Contrarily to the our results, Tokgöz et al (2015) indicated that grafting increased the amounts of K and Mg in the watermelon fruits.…”
Section: Resultssupporting
confidence: 86%
“…Also, Ruiz et al (1996) reported that rootstocks could be responsible for an improvement in the various morphological and physiological characteristics by increasing the P absorption from the soil and its transportation into the plant. On the other hand, Tokgöz et al (2015) reported that the amount of watermelon fruit P was unaffected or minimal by grafting.…”
Section: Resultsmentioning
confidence: 99%
“…A study was conducted on some physical and chemical parameters of the grafted seedling. As the result, it was provided advantages for these mineral matters such as P, K, Ca, Mg, Fe, Zn and Mn in grafted watermelon plants compared to non-grafted [25,31]. However, the literature lacks information about proper scion-rootstock seedling quality combinations for increasing the quality of grafted melon seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…The producers harvesting in June obtain higher yield, therefore, harvesting in June can be recommended to the regional watermelon producers. The results of Tokgöz et al (2015), who evaluated some quality parameters of two different watermelon cultivars grafted on three different rootstocks and harvested at two different times. It has been stated that the use of grafted seedlings provides an advantage in terms of mineral matter, and the samples taken from the second harvest period are more advantageous than the first harvest period.…”
Section: Figure 1 Regression Tree Of Factors Affecting Watermelon Yieldmentioning
confidence: 99%